KECEMASAN KOMUNIKASI PADA MAHASISWA TAHUN PERTAMAILMU KOMUNIKASI - Khoirun Nisa, - (2023)
Proses transisi dari siswa menjadi mahasiswa dan menyesuaikan diri dengan lingkungan akademis yang baru dapat memberikan tantangan besar bagi mahasiswa tahun pertama. Tujuan utama dari penelitian ini adalah untuk menilai tingkat kecemasan komunikasi yang dialamai oleh mahasiswa dan menyelidiki berbagai elemen yang berkontribusi terhadap kecemasan ini. Penulis mengumpulkan data dari 106 mahasiswa jurusan Ilmu Komunikasi di sebuah universitas di Indonesia. Untuk mencapai tujuan penelitian, pendekatan dengan metode campuran digunakan. Setelah menganalisis data kuantitatif dengan Personal Report of Communication Apprehension (PRCA-24) milik McCroskey, wawancara kualitatif dilakukan untuk memperoleh pemahaman komprehensif mengenai pengalaman kecemasan komunikasi mahasiswa. Temuan menunjukkan bahwa mayoritas mahasiswa tahun pertama Ilmu Komunikasi menunjukkan tingkat kecemasan komunikasi sedang. Dengan kepribadian individu dan ketakutan terhadap reaksi orang lain ditemukan sebagai faktor utama tingginya tingkat kecemasan komunikasi. Dalam konteks kecemasan komunikasi mahasiswa, diakui secara luas bahwa pengalaman individu dan pengaruh lingkungan sekitar merupakan faktor yang berkontribusi secara signifikan. Kata Kunci: Indonesia, Kecemasan komunikasi , Mahasiswa, M ahasiswa tahun pertama , PRCA-24 Transitioning from being a high school student to a university student and adjusting to an entirely new academic setting can provide considerable challenges for first year university students. The main objectives of this study was to assess the degree of communication anxiety experienced by college students and investigate the various elements that contribute to this anxiety. The authors collected the data from a total sampling of 106 undergraduate students pursuing a major in Communication Science at a university in Indonesia. To achieve the research objectives, a mixed-methods approach was utilized. After analyzing the quantitative data with McCroskey's Personal Report of Communication Apprehension (PRCA-24), qualitative interviews were conducted to obtain a comprehensive understanding of the students' communication anxiety experiences. The findings indicated that a majority of first-year students enrolled in the field of Communication Science exhibited a moderate degree of communication anxiety. Notably, the primary contributors to heightened levels of anxiety were found to be individual personality traits and apprehension regarding the reactions of others. In the context of students' communication anxiety, it is widely acknowledged that both individual experience and the influence of the surrounding environment are significant contributing elements. Keyword: Communication Anxiety, First- year students, Indonesia, PRCA-24, University students